Solanum anguivi Lam. fruits’ nutritional quality and potential effect on type 2 diabetes mellitus - Nakitto, Aisha Musaazi Sebunya; Justus Liebig University Giessen (My University, 2022)
The burden of diabetes is enormous due to its rapidly increasing global prevalence resulting from lifestyle and dietary habits changes. Although drugs have been developed to treat type 2 diabetes mellitus (T2DM), they are often accompanied by several side effects, and yet they are also expensive. Solanum anguivi Lam. fruits (SALF) are traditionally consumed as a remedy for T2DM. This may be attributable to the presence of bioactive compounds such as phenolics, flavonoids, saponins, alkaloids, and vitamin C in SALF. It has been documented that the nutritional quality of fruits and vegetables may vary among accessions and ripeness stages or may be affected by thermal treatments. However, the data on the influence of accession and ripeness stage and the effect of thermal treatments on the nutritional quality of SALF is scarce. There is also a dearth of data regarding the potential antidiabetic effect of dietary SALF and its underlying mechanisms of action. The present study assessed the bioactive compounds content (BCC) and antioxidant activity (AA) of different SALF accessions and determined the relationships between SALF BCC, AA, and plant morphological characteristics. The influence of the ripeness stage (unripe, yellow, orange, and red) on the BCC and AA of SALF accessions was investigated. The effect of drying temperature (35, 55, and 85 oC) and cooking method (boiling and steaming) and duration (15, 30, 45, 60, and 120 min) on the BCC and AA of SALF accessions were also investigated. The study further explored the potential of dietary SALF to prevent (prevention study) and manage T2DM-like phenotypes (therapeutic study) using the fruit fly, Drosophila melanogaster (D. melanogaster) model, whose energy metabolism has been suggested to be seemingly comparable with humans. The D. melanogaster has also been reported to possess a high number of genes also conserved in humans (including those for the insulin/insulin-like growth factor signaling pathway) and to develop a T2DM-like phenotype upon the intake of a high-sugar diet (HSD). Several metabolic parameters and physiological responses to nutrition have been reported to be dependent on the sex of an animal. In D. melanogaster, a sexually dimorphic response to HSD intake has been reported. Hence, male and female flies were used to determine whether the protective effects of SALF are sex-dependent. In the present study, morphological characterisation, including eleven traits for leaves, stems, and fruits from 12 plants per accession, was assessed based on the descriptors of Solanum species. The BCC was determined by spectrophotometry (for total phenolics, flavonoids, saponins, and vitamin C), HPLC (for quantification of phenolics), and gravimetry (for total alkaloids). The AA, assessed as free radical scavenging activity (FRSC) and total antioxidant capacity (TAC) was also determined by spectrophotometry. For the therapeutic and prevention studies, male and female D. melanogaster were separately exposed to HSD to induce a T2DM-like phenotype. Flies fed on SY10 medium served as the control. In the T2DM therapeutic study, flies were pre-exposed to HSD or control diet for 10 days, followed by an exposure to either HSD supplemented with 5 (HSD+SALF5) or 10 (HSD+SALF10) mg/ml SALF, HSD, or control diet until day 24. To assess whether a T2DM-like phenotype may be prevented by an exposure to HSD supplemented with SALF, male and female flies were reared on control, HSD, HSD+SALF5, or HSD+SALF10 for 24 days. The effect of HSD and HSD+SALF on weight, climbing activity, glucose, and triglyceride contents, survival, and gene expression of the PPARγ co-activator 1α (PGC-1α) fly homolog Srl and the Drosophila insulin-like peptides (dIlp) 3 and 5 were investigated. The weights and climbing activity of the flies were assessed on day 24, while survival was recorded every other 2-3 days when the flies were switched to fresh medium. Furthermore, glucose and triglyceride contents as well as mRNA levels of Srl and dIlp 3 and 5, were analyzed. The morphological characteristics of Solanum anguivi Lam. varied among the accessions investigated in this study. The BCC and AA of the fruits (SALF) significantly differed among the accessions. All investigated SALF accessions were rich in total phenolics, flavonoids, saponin, vitamin C, and alkaloids, compared to foods that have been documented as rich sources of these compounds. Clusters derived for the accessions based on morphological characteristics or chemical content had some similarities. The ripeness stage significantly affected the BCC and AA of SALF, and this significantly differed among accessions. The highest total contents of phenolics and flavonoids, and the highest AA were present at the unripe stage. Additionally, the highest total flavonoid and saponin contents were present at the orange stage, and the highest vitamin C (for some accessions) and alkaloid contents were present at the red stage. Comparison with the red stage of SALF accessions at the unripe stage contained higher amounts of total phenolics (up to 39% higher), flavonoids (up to 15% higher), and AA (by 49-94%). SALF at the red stage, however, had 17-79% higher total alkaloids than the unripe stage, while at the orange stage up to 45% higher total saponins were present compared to the unripe stage. The HPLC results revealed that during ripening, the content of chlorogenic and caffeic acids reduced, gallic acid and rutin increased, while the effect on quercetin levels varied among the accessions. The regression models showed that SALF AA was mostly affected by total phenolic content (TPC) and vitamin C content (VCC) at the unripe stage; TPC and total flavonoid content (TFC) at the yellow stages; TFC and total saponin content (TSC) at the orange stage; and TFC and total alkaloids at the red stage. Thermal treatments significantly affected the BCC and AA of SALF. The drying temperature that resulted in the highest increase of TPC and AA in the SALF samples was 35 oC (2-fold), while 85 oC resulted in little to no increase of TPC and a significantly lower AA than the control (raw/undried SALF). Chlorogenic acid, caffeic acid, and rutin contents were higher at a drying temperature of 35 oC versus 85 oC, while the reverse was true for the gallic acid content. The effect of the drying temperature on the quercetin content varied with accession and ripeness stage. Drying significantly reduced the VCC and TFC compared to the control, and the drying temperature with their highest retention was 35 oC. The effect of drying on total alkaloids and saponins was dependent on the accession and ripeness stage. Similar to drying, both steaming and boiling significantly reduced the VCC. The cooking parameters also significantly reduced the TSC, except 15 min of boiling, which did not affect it. The total alkaloids in SALF were significantly reduced by steaming and increased by boiling. However, a very long cooking duration (120 min) increased the alkaloids 1.5-fold by steaming and 2-fold by boiling. Total flavonoids were not affected by both steaming and boiling, except for 15 min of boiling, which significantly increased the content. Boiling and steaming increased the TPC and AA of SALF up to 4-fold and 3-fold, respectively. Overall boiling resulted in the highest TPC and AA increment of SALF among the investigated thermal treatments in this study, with 15 min (of boiling) as the shortest duration with the highest TPC and AA. However, SALF that was boiled (for 15 min) and then dried (at 35 oC) had higher AA than SALF that was either boiled or dried only. The study revealed positive correlations between AA and the total contents of phenolics, flavonoids, and saponins SALF as well as negative correlations between AA and the contents of vitamin C and alkaloids were shown. The T2DM therapeutic study revealed that SALF supplementation in HSD did not alter the weights, fitness, and triglyceride levels of male and female flies in comparison with the HSD-fed and control-fed flies. The HSD-fed female flies exhibited elevated glucose levels, which significantly decreased in a dose-dependent manner upon exposure to SALF-supplemented HSD. This glucose-lowering effect of SALF may be due to the presence of saponins and phenolics, which have been associated with hypoglycaemic effects in mice. Female flies fed on a SALF-supplemented HSD exhibited a significant increase in survival compared to corresponding HSD-fed and control diet-fed flies. To unravel the underlying protective mechanism of SALF, central genes of the fly’s energy metabolism were investigated. The mRNA levels of Srl decreased in HSD-fed female flies compared to the control-fed, while no effect was observed in females exposed to HSD+SALF. This observation may also explain the unaltered weights and fitness of female flies exposed to HSD+SALF as upregulation of Srl has been associated with weight gain and increased fitness. While the expression of dIlp3 was not changed in all groups of female flies, dIlp6 was significantly induced in female flies by HSD+SALF5 relative to the control, suggesting a central role for dIlp6 in mediating the induction of survival of D. melanogaster by SALF. An increased survival following exposure to HSD+SALF in male flies previously reared on HSD was also observed but without any effects on the glucose levels suggesting that dietary SALF counteracts the HSD-mediated decrease in survival. Similar to the therapeutic study, the weights, triglyceride, and fitness levels of flies in the T2DM prevention study were not affected. However, both male and female flies exposed to HSD supplemented with SALF exhibited higher survival rates than flies exposed to HSD only, which was, however, not reflected in the glucose levels. SALF may protect the flies from a HSD-induced decrease in survival. This lower survival in HSD-fed flies may be similar to premature mortality that has been documented for humans suffering from T2DM. The increased survival of flies exposed to HSD supplemented with SALF may be attributed to the presence of phenolics such as chlorogenic acid and quercetin, which have been reported to increase lifespan in D. melanogaster. In the present study, D. melanogaster fed on HSD+SALF benefited from the consumption of SALF, as reflected in the significant increase in survival. In conclusion, morphological characteristics of Solanum anguivi Lam. accessions may be used to predict SALF accessions with similar BCC and AA. The unripe stage of SALF had the highest AA and TPC and thus may have the highest health-promoting properties. Combined thermal treatments (boiling for 15 min and drying at 35 oC) may mediate the strongest health benefits as they resulted in the highest AA increment of all investigated thermal treatments. The dietary intake of SALF significantly lowered the glucose levels and increased the survival of D. melanogaster, which was, however, not sex-dependent. Additional studies in higher organisms, including humans, are needed to unravel the underlying mechanisms of the therapeutic and preventive effects of dietary SALF and its potential use in the management and treatment of T2DM.
Keywords: Solanum anguivi; Nutritional quality; African eggplant; Forest bitter berry; Drosophila melanogaster; Thermal processing; Type 2 diabetes mellitus; Ripeness stages; Bioactive compounds; Survival; Glucose metabolism; Lifespan; ddc:500; ddc:570; ddc:580; ddc:610; ddc:630